Development and validation of a successful microbiological agar assay for determination of ceftriaxone sodium in powder for injectable solution - Aléssio, Patrícia V. [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (MDPI, 2012)
Ceftriaxone sodium is a cephalosporin with broad-spectrum antimicrobial activity and belongs to the third generation of cephalosporins. Regarding the quality control of medicines, a validated microbiological assay for the determination of ceftriaxone sodium in powder for injectable solution has not been reported yet. This paper reports the development and validation of a simple, accurate and reproducible agar diffusion method to quantify ceftriaxone sodium in powder for injectable solution. The assay is based on the inhibitory effect of ceftriaxone sodium on the strain of Bacillus subtilis ATCC 9371 IAL 1027 used as test microorganism. The results were treated statistically by analysis of variance and were found to be linear (r = 0.999) in the selected range of 15.0-60.0 μg/mL, precise with a relative standard deviation (RSD) of repeatability intraday = 1.40%, accurate (100.46%) and robust with a RSD lower than 1.28%. The results demonstrated the validity of the proposed bioassay, which allows reliable ceftriaxone sodium quantitation in pharmaceutical samples and therefore can be used as a useful alternative methodology for the routine quality control of this medicine. © 2012 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Bioassay; Ceftriaxone sodium; Cephalosporins; Validation; ceftriaxone; accuracy; agar diffusion; Bacillus subtilis; bacterial strain; drug determination; drug structure; growth inhibition; injection; nonhuman; powder; quality control; reproducibility; validation process